Research and Perspectives in Endocrine Interactions
DOI: 10.1007/978-3-540-79288-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Mechanisms Underlying the Intergenerational Transmission of Maternal Behavior and Infant Abuse in Rhesus Macaques

Abstract: SummaryParenting style in rhesus macaques (Macaca mulatta) can vary dramatically among individuals along the two orthogonal dimensions of maternal protectiveness and maternal rejection. High rates of maternal rejection can be accompanied by infant abuse. We investigated the effects of exposure to variable parenting styles on offspring behavioral and neuroendocrine development to identify the possible mechanisms underlying the intergenerational transmission of maternal behavior and infant abuse. Forty-three non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Studies have shown that females, on average, exhibit higher levels of HPA axis activity (Young, Korszun, Figueiredo, Banks-Solomon, & Herman, 2007) and lower levels of serotonin activity than males (Biver et al, 1996;Fischette, Biegon, & McEwen, 1983;Rubinow, Schmidt, & Roca, 1998). Further, nonhuman primate research has revealed that maltreated subjects who carry a copy of the short allele exhibit lower levels of 5-hydroxyindoleacetic acid, exhibit higher levels of ACTH responses to stress, and exhibit more aggressive and anxious behaviors in response to stress than maltreated subjects who do not carry a copy of the short allele (Maestripieri, 2005;McCormack et al, 2009). These negative effects have been shown to be more pronounced for females than males (Barr, Newman, Schwandt, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that females, on average, exhibit higher levels of HPA axis activity (Young, Korszun, Figueiredo, Banks-Solomon, & Herman, 2007) and lower levels of serotonin activity than males (Biver et al, 1996;Fischette, Biegon, & McEwen, 1983;Rubinow, Schmidt, & Roca, 1998). Further, nonhuman primate research has revealed that maltreated subjects who carry a copy of the short allele exhibit lower levels of 5-hydroxyindoleacetic acid, exhibit higher levels of ACTH responses to stress, and exhibit more aggressive and anxious behaviors in response to stress than maltreated subjects who do not carry a copy of the short allele (Maestripieri, 2005;McCormack et al, 2009). These negative effects have been shown to be more pronounced for females than males (Barr, Newman, Schwandt, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Bennett et al's (2002) analysis of 132 rhesus macaques revealed that subjects who carried a short allele and who experienced maternal separation had lower cerebrospinal fluid 5-hydroxyindoleacetic acid concentrations than separated subjects who did not carry a short allele. Lower serotonin activity resulting from the interaction of 5-HTTLPR and maltreatment is somewhat expected given the animal literature that (a) maltreatment is associated with lower levels of serotonin (Champagne & Curley, 2009;Ichise et al, 2006;Maestripieri, 2005;Matthews, Dalley, Matthews, Tsai, & Robbins, 2001) and (b) the short allele of 5-HTTLPR is associated with lower levels of overall serotonin activity (Williams et al, 2001), by way of the short allele leading to fewer serotonin transporters, less reuptake of serotonin from the synaptic cleft, and the subsequent downregulation of postsynaptic receptors (David et al, 2005;Lesch et al, 1996). The lack of inhibition that may arise from lower serotonin activity, coupled with a greater sensitivity to stress from a hyperactive HPA axis, may increase the likelihood that maltreated individuals who carry the short allele will engage in disruptive and maladaptive behaviors (i.e., substance use, depression; Andersen & Teicher, 2009).…”
mentioning
confidence: 98%
“…Suomi's research with rhesus monkeys that are either reared by their mothers or by much less nurturant peers finds that peer-reared males exhibit greater externalizing behavior in adolescence (Suomi, 1997). In research with rhesus macaque monkeys, Maestripieri and colleagues have examined neurobehavioral effects of maternal abuse and neglect on offspring (Maestripieri, 2008). They also find that maternal maltreatment is transmitted by behavior rather than genetics.…”
Section: The Role Of Early Stressors In Predisposing Children To Adolmentioning
confidence: 99%
“…Moreover, the abused females, both crossfostered and non-crossfostered, who became abusive mothers had lower CSF 5-HIAA concentrations than the abused females who did not become abusive mothers (Maestripieri et al, 2006a). This finding suggests that experience-induced, long-term alterations in serotonergic function in females reared by abusive mothers may contribute to the manifestation of abusive parenting in adulthood (Maestripieri, 2008b). …”
Section: Serotoninmentioning
confidence: 98%